Prospect theory, mitigation and adaptation to climate change - Daniel Osberghaus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Climate change is one of the most pressing challenges in current environmental policy. Appropriate policies intended to stimulate efficient adaptation and mitigation should not exclusively rely on the assumption of the homo oeconomicus, but take advantage of well-researched alternative behavioural patterns. Prospect theory provides a number of climate-relevant insights, such as the notion that evaluations of outcomes are reference dependent, and the relevance of perceived certainty of outcomes. This paper systematically reviews what prospect theory can offer to analyse mitigation and adaptation. It is shown that accounting for reference dependence and certainty effects contributes to a better understanding of some well-known puzzles in the climate debate, including (but not limited to) the different uptake of mitigation and adaptation amongst individuals and nations, the role of technical vs. financial adaptation, and the apparent preference for hard protection measures in coastal adaptation. Finally, concrete possibilities for empirical research on these effects are proposed.
Keywords: 330; Adaptation; Climate Change; Mitigation; Prospect Theory; Reference Point; Uncertainty